Preparation of Ag nanoparticles via pulsed laser ablation in liquid for biological applications - Ammar M. Noori (Iraqi Journal of Physics, 2019)
Ag nanoparticles were prepared using Nd:YAG laser from Ag matel in distilled water using different energies laser (100 and 600) mJ using 200 pulses, and study the effect of the preparation conditions on the structural characteristics of and then study the effect of nanoparticles on the rate of killing the two types of bacteria particles (Staph and E.coli). The goal is to prepare the nanoparticle effectively used to kill bacteria.